Investigation, audit and action request submitted to the Washington State Auditor and the Washington State Attorney General concerning the Spokane Transit Authority CenterPlace transaction March 29, 1990 (Spokane Research & Defense Fund, 1991)
Request to the Washington State Auditor and Attorney General to investigate the proposed transaction between the Spokane Transit Authority and CenterPlace to build a transit center in downtown Spokane.